STRATEGI USAHA MIKRO KECIL DAN MENENGAH (UMKM) MELALUI DIGITAL MARKETING DI KECAMATAN BALARAJA PADA ERA PANDEMI COVID-19 - Fahma Islami (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2023)
The ongoing crisis during the pandemic has put even more pressure on MSMEs to survive so they can still make sales. However, circumstances like this also make not a few MSMEs have to go out of business. As MSME actors, there are many factors that can support a business to keep it running, especially during a pandemic like this. One of the most important factors is the marketing strategy. This research was conducted using a qualitative method. Data collection was carried out through observation, interviews and document research and related previous literature studies. There are many ways that MSME players in Balaraja can do to survive during a pandemic like this. Every MSME actor has his own way according to the goods being sold. The findings in this study refer to how to implement target buyer segmentation, which is the first and most important thing before running a business, convincing buyers that our products are safe and of good quality, because quality determines how much sales increase, businesses must innovate, with innovation make the products sold have their own characteristics, have a good relationship with customers, because the customer is the one that will make the business survive, make attractive promos, understand digital marketing and implement digital marketing in MSMEs.